BANK LENDING OF INDUSTRIAL ENTERPRISES: ECONOMIC NATURE AND PRINCIPLES OF ITS REALIZATION - Herasymenko , Alina (Socio-economic relations in the digital society, 2021)
Abstract. Industrial enterprises and banks operate in the conditions of modern realities which reflect the consequences of prolonged socio-economic and political instability. Industrial sector of economy is the object of strategically importance of the state development in developed countries all over the world. At the same time, the industrial sector of economy is tended to be very sensitive to any fluctuations in the both financial and commodity markets, as well as to changing scenarios in the socio-economic and political environments. There are also a number of essential obstacles that hinder development of the former Soviet Union industrial enterprises’ productive and economic potential. Here is some of it: outdated material and technical base, lack of innovative technologies, lack of their own financial resources, high level of energy consumption, poor understanding of the ecology policy issue or its absence, and so on. Such a state reduces the chances of successful development of industrial enterprises’ productive and economic potential significantly. One of the efficient and forceful ways of improvement of overall socio-economic situation in the country is development, stable support and modernization of industrial enterprises on the basis of mutually beneficial cooperation of banks’ and industrial enterprises’ capitals. A special role in these processes should be given to a variety of instruments of financial and credit markets. One of these instruments is a bank lending to industrial enterprises. Herewith, the main accent should be made on the role of bank lending to industrial enterprises. Since any elaboration of subject first of all requires a strong opinion of its economic nature, the term «bank lending to industrial enterprises» is researched in this issue, as well as specific principles of bank lending to industrial enterprises. Keywords: industry, industrial enterprise, loan, lending to enterprises, lending to industrial enterprises, bank lending to industrial enterprises. JEL Classification G21, E51, P42 Formulas: 0; fig.: 2; tabl.: 0; bibl.: 21.